Deterring terrorism: a model for strategic deterrence - Lieberman, Elli (Contemporary terrorism studies, 2018)
Cover; Half Title; Title Page; Copyright Page; Dedication; Table of Contents; List of illustrations; About the contributors; Acknowledgements; Introduction; A roadmap to this volume; Notes; 1. A theoretical introduction; The state of the literature; Deterrence success -- elusive; Deterrence success -- marginal; Understanding deterrence; Cumulative deterrence as teaching moments -- escaping the attrition trap; Resolving the credibility problem and VNSAs' life cycle stages; Methodology -- studying deterrence in enduring terrorist campaigns; Notes; Bibliography